Clustered surface amino acid residues modulate the acid stability of GH10 xylanase in fungi - Xia, Yanwei; Wang, Wei; Wei, Yaning; Guo, Chuanxu; Song, Sisi; Cai, Siqi; Miao, Youzhi (Applied microbiology and biotechnology, 2024)
Acidic xylanases are widely used in industries such as biofuels, animal feeding, and fruit juice clarification due to their tolerance to acidic environments. However, the factors controlling their acid stability, especially in GH10 xylanases, are only partially understood. In this study, we identified a series of thermostable GH10 xylanases with optimal temperatures ranging from 70 to 90 °C, and among these, five enzymes (Xyn10C, Xyn10RE, Xyn10TC, Xyn10BS, and Xyn10PC) exhibited remarkable stability at pH 2.0. Our statistical analysis highlighted several factors contributing to the acid stability of GH10 xylanases, including electrostatic repulsion, π-π stacking, ionic bonds, hydrogen bonds, and Van der Waals interactions. Furthermore, through mutagenesis studies, we uncovered that acid stability is influenced by a complex interplay of amino acid residues. The key amino acid sites determining the acid stability of GH10 xylanases were thus elucidated, mainly concentrated in two surface regions behind the enzyme active center. Notably, the critical residues associated with acid stability markedly enhanced Xyn10RE’s thermostability by more than sixfold, indicating a potential acid-thermal interplay in GH10 xylanases. This study not only reported a series of valuable genes but also provided a range of modification targets for enhancing the acid stability of GH10 xylanases. Key points • Five acid stable and thermostable GH10 xylanases were reported. • The key amino acid sites, mainly forming two enriched surface regions behind the enzyme active center, were identified responsible for acid stability of GH10 xylanases. • The finding revealed interactive amino acid sites, offering a pathway for synergistic enhancement of both acid stability and thermostability in GH10 xylanase modifications.